Preconceived stakeholders' attitude toward telepathology: Implications for successful implementation - Elahe Gozali; Reza Safdari; Malihe Sadeghi; Marjan Ghazi Saeidi; Sharareh R Niakan Kalhori; Farahnaz Noroozinia; Zahra Zare Fazlollahi; Bahlol Rahimi (Elsevier, 2017)
Introduction: Telepathology is a subdiscipline of telemedicine. It has opened new horizons to pathology, especially to the field of organizing consultations. This study aims to determine the capabilities and equipment required for the implementation of telepathology from the viewpoints of managers, IT professionals, and pathologists of the hospitals of West Azerbaijan, Iran. Methods: This is a descriptive-analytical study conducted as a cross-sectional study in 2015. All public and private hospitals of West Azerbaijan were selected as the study sites. The population of the study was the managers, directors, pathologists, and IT professionals of the hospitals. The study population was considered as the study sample. Data were collected using questionnaires. The validity and reliability of the questionnaires were assessed, and data were analyzed using SPSS (Statistical Product and Services Solutions, version 16.0, SPSS Inc, Chicago, IL, USA). Results: The mean awareness of the study population of telepathology in the studied hospitals was 2.43 with a standard deviation of 0.89. According to analysis results (F = 7.211 and P = 0.001), in the studied hospitals, the mean awareness of pathologists, managers, directors, and IT professionals' of telepathology is significant. In addition, the mean awareness of pathologists is higher than that of managers, directors, and IT professionals, and this relation is significant (P = 0.001). According to IT professionals, among the influential dimensions of the implementation of telepathology in the studied hospitals, the effect of all dimensions, except hardware capabilities, was above moderate level. Conclusion: According to our findings, stakeholders believe that the implementation of telepathology promotes the quality of health-care services and caring patients on the one hand and decreases health-care costs on the other hand. Therefore, it crucial and important to consider users' viewpoints into the process of implementing such systems as they play a vital role in the success or failure, and the accurate estimation of required sources, of the systems.